Formula Optimization of Roselle Flower Extract as Clay Facial Soap - Hidayah Anisa Fitri; Ghaliyah Kusuma Wardani; Ika Yuni Astuti; Indri Hapsari (JRST (Jurnal Riset Sains dan Teknologi), 2025)
Roselle flower is known rich in anthocyanin compounds that has activities as antipollutants, so it has potential to be developed as clay facial soap. Soap is formed by the saponification reaction between fatty acids and strong bases which generally has high pH properties. The anthocyanin compound in roselle extract is unstable at base pH. In addition, there are crucial parameters such as pH, viscosity and foam stability that must be eligible to be accepted as cleanser product for facial skin. This study aimed to obtain an optimal formula for clay facial soap containing roselle flower extract by optimizing concentration of surfactant SLES and KOH as soap-forming components. Soap basis was made by mixing the base with fatty acid phase. Design Expert 13 software, one-way ANOVA, and T-Test SPSS were used to design, analyze the effect and predict optimum mixed components in the formula so the final product met the ideal parameters. The data of study showed that the optimal formula of roselle flower clay facial soap should have 9.5% of SLES and 5.25% KOH with a desirability value of 1. The optimum formula had organoleptic, homogeneity, pH, viscosity and foam stability parameters that met the requirements.